Reading Alice Munro, 1973-2013 - Robert Thacker (University of Calgary Press, 2016)
In Reading Alice Munro, 1973-2013, the world's leading Munro scholar offers a critical overview of Alice Munro and her writing spanning forty years. Beginning with a newly written overarching introduction, featuring directive interleaved commentaries addressing chronology and contexts, ending with encompassing afterword, this collection provides a selection of essays and reviews that reflect their times and tell the story of Munro's emergence and recognition as an internationally acclaimed writer since the 1970s. Acknowledging her beginnings and her persistence as a writer of increasingly exceptional short stories, and just short stories, it treats her career through Thacker's criticism up to her fourteenth collection, Dear Life (2012), and to the 2013 Nobel Prize in Literature. Altogether, this book encompasses the whole trajectory of Munro's critical presence while offering a singularly informed retrospective perspective.
English
Keywords: Literary criticism; Biography